2021
DOI: 10.3389/fonc.2021.686792
|View full text |Cite
|
Sign up to set email alerts
|

The Inflammatory Profile of the Tumor Microenvironment, Orchestrated by Cyclooxygenase-2, Promotes Epithelial-Mesenchymal Transition

Abstract: The tumor microenvironment (TME) corresponds to a complex and dynamic interconnection between the extracellular matrix and malignant cells and their surrounding stroma composed of immune and mesenchymal cells. The TME has constant cellular communication through cytokines that sustain an inflammatory profile, which favors tumor progression, angiogenesis, cell invasion, and metastasis. Although the epithelial-mesenchymal transition (EMT) represents a relevant metastasis-initiating event that promotes an invasive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 159 publications
0
25
0
Order By: Relevance
“…In the context of TME, regulatory T cells (Tregs) promote tumor development by dampening anti-tumor immune responses, whereas effector T cells promote inflammation. 71 ENO1 plays a key role in the regulation of T cell effector functions, including T cell activation 72 and the suppressive functions of induced Tregs. 73 Interestingly, downregulation of ENO1 activity represses the glycolytic activity of tumor-infiltrating CD8+ lymphocytes (CD8+ TILs), leading to their functional exhaustion.…”
Section: Eno1 Deregulates Cellular Energetics In Tumor Cellsmentioning
confidence: 99%
“…In the context of TME, regulatory T cells (Tregs) promote tumor development by dampening anti-tumor immune responses, whereas effector T cells promote inflammation. 71 ENO1 plays a key role in the regulation of T cell effector functions, including T cell activation 72 and the suppressive functions of induced Tregs. 73 Interestingly, downregulation of ENO1 activity represses the glycolytic activity of tumor-infiltrating CD8+ lymphocytes (CD8+ TILs), leading to their functional exhaustion.…”
Section: Eno1 Deregulates Cellular Energetics In Tumor Cellsmentioning
confidence: 99%
“…In breast cancer there is a well-established paradigm of elevated COX-2, low 15-PGDH, increased PGE 2 , and associations with more aggressive disease and negative outcomes ( 43 , 44 , 46 49 ). COX-2 overexpression induces tumorigenesis via PGE 2 production, increased angiogenesis ( 42 ), and suppressed tumor immunity ( 40 , 43 45 , 50 , 51 ). In patient tumors, COX-2 overexpression is associated with poor prognoses and lower distant disease-free survival time ( 52 ).…”
Section: Prostaglandin E2 In Cancermentioning
confidence: 99%
“…As the primary mediator of the oncogenic effects of COX-2, PGE 2 -induced receptor signaling contributes to almost all of the major cancer hallmarks, including angiogenesis, proliferation, epithelial-mesenchymal transition (EMT), and the maintenance of CSC characteristics (42,43). PGE 2 is the most common prostanoid in the tumor microenvironment (44,45). In breast cancer there is a well-established paradigm of elevated COX-2, low 15-PGDH, increased PGE 2 , and associations with more aggressive disease and negative outcomes (43,44,(46)(47)(48)(49).…”
Section: Prostaglandin E2 In Cancermentioning
confidence: 99%
“…Nevertheless, it has also been described that in a previously detected tumor, not linked to a previous inflammatory process, inflammation is present in the surrounding area of the tumor, promoting cancer progression to achieve the malignant phenotype, tissue remodeling, metastasis, and angiogenesis, or the suppression of immune response [97]. Regarding microenvironmental components, it has been reported that macrophages are the most abundant cells in tumor environments and their function in cancer is contradictory.…”
Section: Inflammation and Cancermentioning
confidence: 99%